2022
DOI: 10.1109/access.2022.3218621
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Early Diagnosis of Alzheimer’s Disease Using 3D Deep Ensemble Approach

Abstract: Alzheimer's disease (AD) is considered the 6 th leading cause of death worldwide. Early diagnosis of AD is not an easy task, and no preventive cures have been discovered yet. Having an accurate computer-aided system for the early detection of AD is important to help patients with AD. This study proposes a new approach for classifying disease stages. First, we worked on the MRI images and split them into an appropriate format to avoid data leakage. Subsequently, a simple and fast registration-free preprocessing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…An augmentation of the ADNI dataset was used to show how effective this process is. With AUC values of 91.28% and 88.42%, respectively, the ensemble technique [28] outperformed previous research in the literature regarding better identification between people with AD and MCI and between MCI and cognitive normal (CN). Additionally, the technique showed that it was possible to differentiate between the three stages of the illness.…”
Section: Unique Mri Formatting For Disease Stagementioning
confidence: 74%
“…An augmentation of the ADNI dataset was used to show how effective this process is. With AUC values of 91.28% and 88.42%, respectively, the ensemble technique [28] outperformed previous research in the literature regarding better identification between people with AD and MCI and between MCI and cognitive normal (CN). Additionally, the technique showed that it was possible to differentiate between the three stages of the illness.…”
Section: Unique Mri Formatting For Disease Stagementioning
confidence: 74%
“…The overall detection accuracy for AD is 94.08%, 96.39%, and 97.51%, respectively. A. Gamal et al [31] discussed the Ensemble Learning (EL) approach for diagnosing AD. The authors used the ADNI dataset consisting of 789 3D MRI images.…”
Section: A Analysis Of Admentioning
confidence: 99%
“…To attain a more accurate and reliable model, researchers propose an ensemble voting approach that combines multiple classifier predictions, yielding impressive results for older individuals in the OASIS data set [43]. This investigation introduces a unique computer-assisted method for early Alzheimer's diagnosis, leveraging MRI images and various 3D classification architectures for image processing and analysis, further enhancing the EL technique's outcomes [44].…”
Section: Recent Studymentioning
confidence: 99%